PELATIHAN PERPAJAKAN UNTUK GURU DAN BENDAHARA MI MUHAMMADIYAH 02 PEKANBARU (MI MUDA) - Jeni Wardi; Zulia Khairani; Imran Al Ucok Nasution (Jurnal Pengabdian Kompetitif, 2026)
Abstract: Schools have a strategic role in forming quality human resources, which must be supported by accountable and transparent financial management, including in the tax aspect. However, in practice, there is still limited understanding of teachers and school treasurers regarding tax obligations, especially regarding the management of BOS funds and the use of the digital tax system. Based on these conditions, a team of lecturers from the Postgraduate School of Lancang Kuning University (Unilak) carried out Community Service activities in the form of Tax Training for teachers and treasurers of MI Muhammadiyah 02 Pekanbaru (MI MUDA). This activity aims to increase participants' competency in understanding school tax obligations as well as technical skills in using the Coretax DJP-based digital taxation system, including registration and activation of the Population Identification Number (NIK) as a tax identity, as well as the use of the e-Bupot and e-Invoice applications. Implementation methods include interactive lectures, discussions, direct practice, and technical assistance. The results of the evaluation of 14 participants showed a significant increase in understanding after the activity, marked by an increase in the participants' ability to understand and apply school tax administration and reporting. This activity makes a real contribution in supporting the implementation of accountable, transparent and professional Good School Governance in partner schools.